Strategi Peningkatan Kompetensi Aparatur Sipil Negara Dalam Rangka Meningkatkan Indeks Reformasi Birokrasi - Banatil Mufidah; Imam Fachruddin; Daimul Abror; Teguh Pramono; Muhamad Chairul Basrun Umanailo (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
The Regional Personnel Agency of Kediri shows data that not all State Civil Apparatuses in the Kediri Regency are placed based on their capabilities and expertise on the expectations and goals of the institution. Some educational backgrounds do not suit the job specifications and often hinder employees from carrying out their tasks. In addition, the rotation and type of positions are different from their abilities and experience. Therefore, a strategy is needed to overcome these problems. Therefore, this study aims to describe and analyze personnel competency improvement strategies to increase the bureaucratic reform index. This is descriptive qualitative research with Miles Hubberman's interactive. Data collection techniques used are interviews, observation, and documentation. The results of the study show that to increase the competency of the state civil apparatus in order to increase the index of bureaucratic reform in Kediri Civil Service Agency, it is carried out through three strategies: technical competence, managerial competence, and socio-cultural competence. These strategies showed significant results in increasing personnel competency as well as the bureaucratic reform index. One of the driving factors is that the leadership and environment have a strong commitment to it. While the inhibiting factor is the lack of information about personnel competency training due to the absence of a memorandum of understanding with some agencies.